New trends in process control and production management : proceedings of the International Conference on Marketing Management, Trade, Financial and Social Aspects of Business (MTS 2017), 18-20 May 2017, Košice, Slovak Republic and Tarnobrzeg, Poland /: proceedings of the International Conference on Marketing Management, Trade, Financial and Social Aspects of Business (MTS 2017), 18-20 May 2017, Košice, Slovak Republic and Tarnobrzeg, Poland. ([2018]) - Unknown
No abstract available